The Effect of Dumble Weight Training and Spring Strength Training on Speed Jab's Punch - Lesmana, Indra; Hermanzoni, Hermanzoni; Argantos, Argantos; Yenes, Ronni (Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
Studi Purpose The problem of this research is that the athletes are less than optimal in doing the speed of the jab. This study aims to determine the effect of dumbbell weight training and spring force training on the speed of the jab. Method This research is a type of quasi-experimental research. This research was carried out at the Andalas Plaza, Padang City. The time of the research implementation is from February 21 to March 21, 2021. The design of this research is